From 'History as Told' to 'History as Experienced': Contextualizing the Uses of the Past. Issue 12 (December 2018) - Lubinski, Christina
Research has made great strides in understanding how and why organizational actors use the past. So far, scholars have largely focused the level of analysis on the organization, without exploring the intertwined nature of historical claim-making with the organizational field or society at large. This article extends the status quo by conceptualizing the role of context for organizational uses-of-the-past. It identifies three key aspects of context that shape how history contributes to the social construction of reality: the existence of multiple audiences, the landscape of pre-existing historical narratives and the experience of social practices giving credibility to historical claims. By analysing the historical case of German business in colonial India, the paper makes three broader claims that could move research toward a more contextualized conception of the uses-of-the-past: (i) historical claims are validated in a continuous dialogue with multiple audiences; (ii) they revise previously existing narratives by critiquing or 'outpasting', i.e. invoking earlier origins; (iii) they often result in 'rhetorical frictions' that require continuous and skilful history revisions to mitigate emerging conflicts in their reception. By contextualizing the uses-of-the-past in this way, the paper moves beyond 'hypermuscular' organizational actors bending history to their will and foregrounds the situated nature of historical rhetoric.